Cross-species microsatellite amplification of river terrapin (Batagur affinis) - Ismail, Nurul Aini; Ab Ghani, Nurul Izza; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Batagur affinis (river terrapin or “tuntung”) is one of the world’s most critically endangered species. It is distributed across Sumatera, Malaysia, Thailand and Cambodia. Its population number is declining in the wild because of habitat destructions and it economic value (i.e. exotic delicacies for eggs and meat). Hence, many reintroduction efforts had been done. Yet, the wild populations are not improving. One of the possible reasons behind this failure is possibly due to low genetic diversity in this species. Thus, population genetics study should be conducted. In this preliminary population genetics study, a total of 33 microsatellite primers from other freshwater terrapin (i.e. B. trivittata and Podocnemis unifilis) were screened and optimised for 30 samples of river terrapin from Kemaman, Terengganu using touchdown protocol and followed by gradient protocol. Among those 33 primers, 23 primers were able to cross-amplify with B. affinis and optimised for annealing temperature (51 – 70°C). Those 23 primers will be used for future population genetics study using samples from both Bota Kanan, Perak and Kemaman, Terengganu.